Genotype x environment interaction effect on grain yield of cowpea (Vigna unguiculata (L.) Walp) in Deciduous forest and Sudan savanna ecologies of Ghana - Francis Kusi; Richard Adu Amoah; Patrick Attamah; Shaibu Alhassan; Damba Yahaya; Justice Frederick Awuku; Jerry A. Nbonyine; Isaac Amegbor; Gloria Mensah; Issah Sugri; Mukhtaru Zakaria; Salim Lamini; et al. (PLoS ONE, 2025)
Cowpea is deemed as a food security crop due to its ability to produce significant yields under conditions where other staples fail. Its resilience in harsh environments; such as drought, heat and marginal soils; along with its nitrogen-fixing capabilities and suitability as livestock feed make cowpea a preferred choice in many farming systems across sub-Saharan Africa (SSA). Despite its importance, Cowpea yields in farmers’ fields remain suboptimal, primarily due to biotic and abiotic factors and the use of either unimproved varieties or improved varieties that are not well-suited to local conditions. Multi environment testing of genotypes is essential for recommending varieties suited for either specific or for wide cultivation. This study aimed, to identify and recommend cowpea breeding lines for wide or specific cultivation in the Sudan Savanna and Deciduous Forest zones of Ghana. The research utilized twenty early-maturing advance cowpea breeding lines and three check varieties (released varieties). The experiment was conducted in two locations: Bunso in the Deciduous Forest zone and Manga in the Sudan Savanna zone over 2020/2021 and 2021/2022 cropping seasons. Combined analysis of variance revealed a significant genotype-environment interaction (GEI) which accounted for 35.12% of the variation in yield. The environments were classified into three mega environments, with Bunso_2021 identified as the near-ideal environment where the genotypes exhibited their maximum genetic potentials. In terms of adaption, genotype UG_04 demonstrated broad adaption, showing high yield and stability across all test environments. Genotypes UG_01 and UG_02 performed particularly well in Bunso_2021 and Bunso_2022, while UG_04 and UG_14 excelled in Manga_2021. These findings provide valuable insights for selecting cowpea varieties that can enhance productivity and stability in diverse agro-ecological zones.